Question
upstudy study bank question image url

\( -\cos \theta=2 \sin ^{2} \theta \) how that the equation can be written as: \( (2 \cos \theta+1)(\cos \theta-1)=0 \) Hence, determine the general solution of \( (2 \cos \theta+1)(\cos \theta-1)=0 \)

Ask by Goodwin Black. in South Africa
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The equation \( -\cos \theta = 2 \sin^2 \theta \) can be rewritten as \( (2 \cos \theta + 1)(\cos \theta - 1) = 0 \). This leads to two solutions: 1. \( \cos \theta = -\frac{1}{2} \), which occurs at \( \theta = \frac{2\pi}{3} + 2\pi k \) and \( \theta = \frac{4\pi}{3} + 2\pi k \) for any integer \( k \). 2. \( \cos \theta = 1 \), which occurs at \( \theta = 2\pi k \) for any integer \( k \). So, the general solutions are: - \( \theta = \frac{2\pi}{3} + 2\pi k \) - \( \theta = \frac{4\pi}{3} + 2\pi k \) - \( \theta = 2\pi k \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Extra Insights

To rewrite the equation \( -\cos \theta = 2 \sin^2 \theta \) using the Pythagorean identity \( \sin^2 \theta = 1 - \cos^2 \theta \), we start with: \[ -\cos \theta = 2(1 - \cos^2 \theta) \] Distributing the 2 gives: \[ -\cos \theta = 2 - 2\cos^2 \theta \] Rearranging the equation results in: \[ 2\cos^2 \theta - \cos \theta - 2 = 0 \] This is a quadratic equation in terms of \( \cos \theta \). To factor it, we look for two numbers that multiply to \( -4 \) (the product of \( 2 \) and \( -2 \)) and add to \( -1 \). The numbers \( -2 \) and \( 1 \) work, allowing us to factor the equation as: \[ (2 \cos \theta + 1)(\cos \theta - 1) = 0 \] Now, solving for \( \theta \): 1. **From \( 2 \cos \theta + 1 = 0 \)**: \[ \cos \theta = -\frac{1}{2} \] The general solutions are: \[ \theta = \frac{2\pi}{3} + 2k\pi \quad \text{and} \quad \theta = \frac{4\pi}{3} + 2k\pi, \quad k \in \mathbb{Z} \] 2. **From \( \cos \theta - 1 = 0 \)**: \[ \cos \theta = 1 \] The general solution is: \[ \theta = 2k\pi, \quad k \in \mathbb{Z} \] Thus, the complete general solution for the original equation is: \[ \theta = \frac{2\pi}{3} + 2k\pi, \quad \theta = \frac{4\pi}{3} + 2k\pi,\quad \text{and} \quad \theta = 2k\pi, \quad k \in \mathbb{Z} \]

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy